Whom are you speaking for? Obstacles to participation encountered by special-seat councillors in Tanzanian Local Councils - Swai, Idda; Zeegers, Nicolle (Gender and Women Studies, 2024)
This is an open access article published by the Rivera in Gender and Women Studies 5(1):3 of 2023.